UMPSA committed to empowering youth spirit and mental health awareness among students - Naqiah, Puaad (UMPSA, 2025)
KUANTAN, 15 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) remains committed to strengthening student development based on holistic values and mental well-being through the organisation of the UMPSA-level National Youth Day Celebration Programme 2025.